2020
DOI: 10.1097/wnp.0000000000000800
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic Seizures in Emergency Department Patients After Treatment for Convulsive Status Epilepticus

Abstract: It is unknown how often and how early EEG is obtained in patients presenting with status epilepticus. The Established Status Epilepticus Treatment Trial enrolled patients with benzodiazepinerefractory seizures and randomized participants to fosphenytoin, levetiracetam, or valproate. The use of early EEG, including frequency of electrographic seizures, was determined in Established Status Epilepticus Treatment Trial participants.Methods: Secondary analysis of 475 enrollments at 58 hospitals to determine the fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…We found that it took a median of 4.2 h for initiation of EEG monitoring which may have decreased our sensitivity to detect ESz and ESE following intubation thus masking any differences in time to seizure occurrence, though the time to initiate EEG monitoring and incidence of ESE we detected was comparable to the literature. [37] This variability in timing of EEG monitoring limited our ability to assess incidence of periodic patterns on EEG, a potentially important factor in patients with primary brain injury. [38] Importantly, we were limited to utilization of clinical EEG reports, rather than raw EEG data, to assess our outcome of interest.…”
Section: Discussionmentioning
confidence: 99%
“…We found that it took a median of 4.2 h for initiation of EEG monitoring which may have decreased our sensitivity to detect ESz and ESE following intubation thus masking any differences in time to seizure occurrence, though the time to initiate EEG monitoring and incidence of ESE we detected was comparable to the literature. [37] This variability in timing of EEG monitoring limited our ability to assess incidence of periodic patterns on EEG, a potentially important factor in patients with primary brain injury. [38] Importantly, we were limited to utilization of clinical EEG reports, rather than raw EEG data, to assess our outcome of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a secondary analysis from the established status epilepticus treatment trial (ESETT) found that only 58% (278/475) of a subgroup of patients had an EEG performed within the first 24 h post-seizure onset, with a median time to EEG recording of 5 h (IQR: 3–10 h) [ 32 ]. Emergent EEGs are infrequently performed in the ED, especially during nighttime and on weekends, primarily due to logistical challenges associated with the application of EEG in the ED, such as limited space, availability of technologists, and a lack of expertise in acute EEG interpretation, compounded by generally low clinical suspicion [ 33 ].…”
Section: Continuous Eeg For Seizure and Status Epilepticus Detectionmentioning
confidence: 99%
“…ABC, airway, breathing and circulation; IV, intravenous; AED, anti-epileptic drug; CBC, complete blood count; CMP, complete metabolic panel; CT, computed tomography; EEG, electroencephalogram; MRI, magnetic resonance imaging; KD, ketogenic diet; rTMS, repetitive transcranial magnetic stimulation; and VNS, vagal nerve stimulator. out' into subtle semiology [5,6], eventually becoming nonconvulsive following initiation of firstor second-line AEDs.…”
Section: Types Of Status Epilepticusmentioning
confidence: 99%
“…Non‐convulsive status epilepticus can present with or without coma, with protean manifestations in a broad range of contexts. This includes a subset of patients presenting with convulsive status epilepticus that transforms or ‘burns out’ into subtle semiology [5, 6], eventually becoming non‐convulsive following initiation of first‐ or second‐line AEDs. Non‐convulsive status epilepticus, even if prolonged, may not require intensive care or anaesthetic management.…”
Section: Types Of Status Epilepticusmentioning
confidence: 99%